COMPARATIVE ANALYSIS OF SHORT VOWELS OF NOUNS’ IN CLASSICAL AND MODERN PERSIAN - Hamitov Dilovar Lutfullozoda (Galaxy International Interdisciplinary Research Journal, 2021)
In the article, the short vowels in classical Persian are compared with the vowels in modern Persian. The reason is that classical Persian was divided into three independent languages in the XIX-XX centuries: modern Persian - in Iran, Tajik - in Tajikistan and Dari - in Afghanistan.Each of these languages has its own characteristics. It also has places that are different from classical Persian.